RHEOLOGICAL AND COMPARATIVE STUDY OF HONEY FROM EUROPEAN BEES (Apis mellífera) AND URUÇU BOCA-DE-RENDA BEES (Melipona seminigra) FROM MARBÁ-PA (REMUNOM, 2025)
Honeys are viscous and sweet substances, appreciated by the population as a food source and as a therapeutic resource. The viscosity of honey is one of the criteria used by the population to choose it, as more viscous honeys (“thicker”) are considered better and pure. The present work sought to determine the viscosity of honeys from European bees and uruçu boca-de-renda, from Marabá, in Pará, in addition to tracing their rheological profiles, at six different temperatures (10º C, 20º C, 30º C, 40º C, 50º C and 60º C). The results demonstrated that the viscosity of the two types of honey reduced with increasing temperature, but as the temperature increased, the difference in viscosity between the two types of honey decreased rapidly. For both types of honey, the 3rd degree function proved to be the best option for modeling viscosity (cSt) versus temperature (o C).